Development of an empirical method for determination of thermal conductivity and heat loss for pre-insulated plastic bonded twin pipe systems - Schuchardt, Georg Konrad (International Journal of Sustainable Energy Planning and Management, 2018)
Pre-insulated twin pipe systems (PTPS) for heat distribution offer advantages for heat supply companies. Trench dimensions for heat supply systems of District Heating (DH) networks might be reduced using these pipe systems. This reduces costs in civil engineering. Additionally heat loss of the DH network may be reduced, that decreases operational costs of these systems. On the other hand, operational heat losses of PTPS significantly differ in many cases from theoretical heat loss of PTPS. This may inhibit the application of this technology in DH networks. Against this background, a standard measurement procedure of thermal properties of PTPS shall be developed, validated and tested at FFI. These tests shall be based on standard measurement procedures for single pipe systems described in EN ISO 8497 and modified for PTPS. Within this context, preliminary tests are done at FFI. Numerical simulations of heat loss are done at IGTH and iteratively fitted to data generated from measurements at the same time. Numerical simulations of stresses occurring due to operational temperatures for PTPS are done in a second step. Internal stresses due to temperature gradients within PTPS as well as external stresses due to interactions of PTPS with the bedding material and ground will be examined. In addition, interactions of bedding materials, operational conditions and heat losses in situ will be assessed. First results obtained are presented in this paper. Focus of this paper is on development of a standard measurement procedure for thermal properties of PTPS, as well as results of numerical calculations regarding heat loss of these systems. One goal of this project funded by the “BMWi – Federal Ministry for Economic Affairs and Energy”, is to discuss and mirror project results in order to modify existing standards, e.g. EN 15698, EN 15632 and EN 13941. Defined quality standards for PTPS, verified by standardized measurement procedures for PTPS, will increase the acceptance of PTPS in the DH sector. This supports small and medium sized enterprises (SME) using and producing PTPS.